Mandibular Movements As Accurate Reporters of Respiratory Effort during Sleep: Validation against Diaphragmatic Electromyography - Martinot, Jean-Benoît; Le-Dong, Nhat-Nam; Cuthbert, Valerie; Denison, Stephane; Silkoff, Philip E.; Guénard, Hervé; Gozal, David; Pepin, Jean-Louis; Borel, Jean-Christian (Frontiers in Neurology, 2017)
Context: Mandibular movements (MM) are considered as reliable reporters of respiratory effort (RE) during sleep and sleep disordered breathing (SDB) but MM accuracy has never been validated against the gold standard diaphragmatic EMG activity (EMG-d). Objectives: To assess the degree of agreement between MM and EMG-d signals during different sleep stages and abnormal respiratory events. Methods: Twenty-five consecutive adult patients with SDB were studied by polysomnography (PSG) that also included multipair oesophageal diaphragm electromyography and a magnetometer to record MM. EMG-d activity (µV) and MM (mm) amplitudes were extracted by envelope processing. Agreement between signals amplitudes was evaluated by mixed linear regression and cross-correlation function (CCF) and in segments of PSG including event-free and SDB periods. Results: The average total sleep time (TST) was 370±18 minutes and the apnea hypopnea index (AHI) was 24.8 ± 5.2 events/hour. MM and EMG-d amplitudes were significantly cross-correlated: median r (95%CI): 0.67 (0.23 to 0.96). A mixed linear model showed that for each 10 µV of increase in EMG-d activity, MM amplitude increased by 0.28 mm. The variations in MM amplitudes (median range: 0.11 to 0.84 mm) between normal breathing, respiratory effort related arousal, obstructive, mixed and central apnea periods closely corresponded to those observed with EMG-d activity (median range: 2.11 to 8.23 µV). Conclusion: MM amplitudes change proportionally to diaphragmatic EMG activity, and accurately identify variations of respiratory effort during normal sleep and SDB.